How Social Media are Changing Hospitality Communications - Wichels, Susana (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2016)
The new information and communication technologies (ICT),in particular Social Media like TripAdvisor, Face-book or Twitter are changing flows, processes and tools in Tourism Communication. Considering that traditional communi-cation tools and strategies are becoming less and less effective, ICT are encouraging new communication practices and influencing consumer behaviour. Several studies from the perspective of the reception have been published in recent years on the impact of Social Media in Tourism, therefore we thought to develop a study from the perspective of production. We approach the features and peculiarities of the impact of 2.0 platforms in Tourism Communication and we present as a case study the communication strategy of Long Beach Hotel, Sun Resorts in Mauritius Islands.